2009
DOI: 10.1016/j.cmet.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Dominant Role of the p110β Isoform of PI3K over p110α in Energy Homeostasis Regulation by POMC and AgRP Neurons

Abstract: SummaryPI3K signaling is thought to mediate leptin and insulin action in hypothalamic pro-opiomelanocortin (POMC) and agouti-related protein (AgRP) neurons, key regulators of energy homeostasis, through largely unknown mechanisms. We inactivated either p110α or p110β PI3K catalytic subunits in these neurons and demonstrate a dominant role for the latter in energy homeostasis regulation. In POMC neurons, p110β inactivation prevented insulin- and leptin-stimulated electrophysiological responses. POMCp110β null m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
167
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(184 citation statements)
references
References 48 publications
12
167
4
1
Order By: Relevance
“…Our findings indicate a dissociated role of distinct PI3K catalytic subunits downstream of leptin signaling, which has also been suggested by studies using chemically defined hypothalamic neurons (14, 20, 21). The metabolic similarities between mice with deletion of PI3K and those with deletion of PTEN in LR cells were intriguing (14,20,21). PTEN is a phosphatase associated with conversion of PIP3 to PIP2, resulting in PI3K inactivation (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings indicate a dissociated role of distinct PI3K catalytic subunits downstream of leptin signaling, which has also been suggested by studies using chemically defined hypothalamic neurons (14, 20, 21). The metabolic similarities between mice with deletion of PI3K and those with deletion of PTEN in LR cells were intriguing (14,20,21). PTEN is a phosphatase associated with conversion of PIP3 to PIP2, resulting in PI3K inactivation (40).…”
Section: Discussionmentioning
confidence: 99%
“…neurons has suggested the existence of dissociated effects of both subunits in energy balance and glucose homeostasis (16,(20)(21)(22), but, again, whether these responses are associated with leptin or insulin signaling has not been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that SOCS3 expression is Cre-dependent, and its expression is upregulated approximately twofold in Cre-expressing cells upon recombination (6). The Tg.Agrp-Cre mice have been used and validated in a number of independent studies (7,(25)(26)(27)(28)(29)(30)(31). The resultant mutant mice, termed AgRP-SOCS3-OE, were born in Mendelian ratio with no detectable gross abnormalities.…”
Section: Expression Of Socs3 In Agrp Neurons Is Dynamically Modulated Inmentioning
confidence: 99%
“…In a recent study, the authors generated a mouse model carrying a conditional deletion of p110α or p110β specifically from cells that express POMC or AgRP (52). As opposed to what was previously suggested, these authors showed that the p110β subunit exerts a dominant role over p110α in the regulation of energy homeostasis.…”
Section: The Catalytic Subunits Of Class Ia Pi3ksmentioning
confidence: 88%
“…This study also emphasized the importance of the p110β subunit for the electrophysiological properties of these neurons, although some controversial points were presented. For instance, POMC-specific deletion of p110α (POMCp110α null) created a more hyperpolarized resting membrane potential, compared to intact POMC neurons (52). Apparently, these changes did not interfere with leptin activity, since leptin depolarized POMCp110α null neurons and increased their spike firing frequency, as observed in intact POMC neurons.…”
Section: The Catalytic Subunits Of Class Ia Pi3ksmentioning
confidence: 97%